Collective levels of stigma and national suicide rates in 25 European countries. (27th February 2014) - Schomerus, G.; Evans-Lacko, S.; Rüsch, N.; Mojtabai, R.; Angermeyer, M. C.; Thornicroft, G.
Abstract : Aims: There is substantial diversity in national suicide rates, which has mainly been related to socio-economic factors, as well as cultural factors. Stigma is a cultural phenomenon, determining the level of social acceptance or rejection of persons with mental illness in a society. In this study, we explore whether national suicide rates are related to the degree of mental illness stigma in that country. Methods: We combine the data on country-level social acceptance (Eurobarometer) with the data on suicide rates and socio-economic indicators (Eurostat) for 25 European countries. Results: In a linear regression model controlling for socio-economic indicators, the social acceptance of someone with a significant mental health problem in 2010 was negatively correlated with age standardised national suicide rates in the same year ( β −0.46, p = 0.014). This association also held true when combining national suicide rates with death rates due to events of undetermined intent. Conclusions: Stigma towards persons with mental health problems may contribute to differences in suicide rates in a country. We hypothesise possible mechanisms explaining this link, including stigma as a stressor and social isolation as a consequence of stigma.